Motif Dakwah Multikultural Abdurrahman Wahid Dalam Pendirian Masjid Cheng-ho - Husnan, Moch; Nur Halimatus (UIN Sunan Ampel Surabaya, 2023)
This study aims to find Abdurrahman Wahid's multicultural da'wah motif approach to Cheng-ho Mosque. Cheng-ho Mosque is a mosque that is quite widely located in Indonesia. This mosque attracts attention because of the combination of architecture and cultural diversity that characterizes it. The focus of the study is to understand the motivation of Multicultural Da'wah behind Abdurrahman Wahid's support for the Cheng-ho mosque. The methods used are qualitative, with a literature analysis approach and a literature study. Conducting this literature review can help avoid repeating research that has been done before and provide in-depth knowledge of Abdurrahman Wahid's thoughts and views on the Cheng-ho mosque. The results show that Abdurrahman Wahid's motives towards the Cheng-ho Mosque are rooted in his beliefs and multicultural approach to spreading Islam. He views the Cheng-ho mosque as a symbol of cultural diversity that can serve as a bridge to strengthen relations between Muslims and non-Muslim communities in Indonesia. Abdurrahman Wahid saw the potential of the Cheng-ho mosque as a place for interfaith dialog, the spread of tolerance values, and the development of social harmony. From the perspective of multicultural da'wah, Abdurrahman Wahid's approach to the Cheng-ho mosque emphasized the importance of inclusion and mutual understanding between religious communities. He promotes the teaching of Islam that is able to appreciate cultural diversity and emphasize the values of interfaith brotherhood. By using the Cheng-ho mosque as a means of da'wah, Abdurrahman Wahid sought to change the paradigm of da'wah from exclusive to inclusive so as to build a more harmonious society.